The presence in the beginning: a gnoseological argument about the difference between Plato and Plotinus (Revista Archai, 2022)
The acceptance of the identity of the Idea of the Good and the One does not necessarily implies that Plato and Plotinus understand it in the same way, as Gerson has recently sustained. The difference, I intend to show, is supported by a gnoseological aspect of their philosophies. Even if both philosophers accept the possibility of arriving at a presence in the principle itself, and even if they use the same erotic metaphor to describe it, this presence means for Plato the flourishing of Nous and the generation of episteme, whereas for Plotinus it is superior to episteme and requires the complete retirement not just of intellection, but also of the desire to think the Good. Correspondingly, Plato considers the Good/One as a Form - as the Form of Forms - at the summit of being and the intelligible realm, while Plotinus conceives it as aneideon, amorphon and apeiron, and therefore, as radically transcendent to being and thinking.